Coefficient of equivalent plastic strain based on the associated flow of the Drucker-Prager criterion. (July 2017) - Ding, Xiang; Zhang, Guangqing
Abstract: This paper proposes a generalized expression for the coefficient of equivalent plastic strain based on the associated flow of the Drucker-Prager criterion for geomeaterials. By conducting triaxial compression tests of sandstone samples in the laboratory, the coefficient of pressure sensitivity α and the shearing cohesion k of sandstone samples are calibrated as functions of the plastic volumetric strain. The coefficient of equivalent plastic strain is dependent on the chosen yield criterion. When the Mises yield criterion is used, the coefficient of equivalent plastic strain equals 2 / 3 . Moreover, the equivalent plastic strain based on the associated flow of the Drucker-Prager criterion is no longer a constant but decreases gradually with the plastic deformation, and its value is always less than 2 / 3 . If the coefficient of equivalent plastic strain based on the associated flow of the Drucker-Prager criterion is taken as 2 / 3, which is a conventional practice and a basis of many finite element software, the computed value of the equivalent plastic strain will significantly deviate from the actual value. Highlights: The coefficient of equivalent plastic strain depends on the yield criterion chosen. A general expression of the coefficient of equivalent plastic strain for associated Drucker-Prager criterion is proposed. The mobilization of strength parameters of Drucker-Prager criterion is calibrated with triaxial compression tests. The evolution of coefficient of equivalent plastic strain of associated Drucker-Prager criterion is presented.